Management of Follow-Up With Preterm Infants During the Outbreak in China - Li, Linlin; Li, Zhenghong; Wan, Weilin; Li, Ji; Zhang, Yu; Wang, Changyan; Wang, Lin (Frontiers in Pediatrics, 2021)
Introduction: Coronavirus disease 2019 (COVID-19) swept Wuhan in January 2020. Other cities in China also suffered during the pandemic. Routine medical services were conducted in the Neonatal Intensive Unit (NICU) as usual, but the follow-up after discharge was seriously affected. Objective: To investigate the feasibility and effectiveness of a combination of online and face-to-face follow-up for preterm infants during the COVID-19 epidemic and to explore a follow-up pattern that can provide follow-up services while maximizing the protection of preterm infants and soothing the fear of their parents. Methods: Preterm infants (n=35) whose first follow-up appointment was scheduled from February 1 to April 30, 2020, and preterm infants (n=43) in the NICU follow-up group who were discharged from January 1, 2018, to January 31, 2020, who had a second or later routine follow-up appointment scheduled from February 1 to April 30, 2020, were enrolled. We provided a combination of online and face-to-face follow-up for preterm infants surveyed with the Wenjuanxing platform before and after the online follow-up and compared the first-time follow-up rate between the outbreak and the same period of the previous year. Results: Feeding and oral medicine and supplements were the most concerning problems of the parents of preterm infants. The anxiety level of the family was significantly decreased after online follow-up (P < 0.05). A total of 96.8% of parents were satisfied or very satisfied with online follow-up, and 95.2% of parents thought that online follow-up had answered all their questions. Only 35.5% of parents thought online follow-up could replace face-to-face follow-up. Conclusion: The combination of online and face-to-face follow-up alleviated the anxiety of the parents during the outbreak and achieved a similar first-time follow-up rate as the same period in 2019.